Ethical Consumption : a Critical Introduction. - Lewis, Tania (Taylor and Francis, 2013)
A not-so-quiet revolution seems to be occurring in wealthy capitalist societies - supermarkets selling 'guilt free' Fairtrade products; lifestyle TV gurus exhorting us to eat less, buy local and go green; neighbourhood action groups bent on 'swopping not shopping'. And this is happening not at the margins of society but at its heart, in the shopping centres and homes of ordinary people. Today we are seeing a mainstreaming of ethical concerns around consumption that reflects an increasing anxiety with - and accompanying sense of responsibility for - the risks and excesses of contemporary lif.